Piezosurgery in maxillary sinus lift (Research, Society and Development, 2022)
In the field of physics, in 1881, the concept of the piezoelectric system began to be studied. This system is widely used in various surgeries in dentistry as well as medicine. The piezoelectric apparatus uses a specific ultrasonic agitation, making it possible to cut only hard tissue, preserving the soft tissues as much as possible, which is very satisfactory, depending on the clinical situation. It allows a safe and specific section, being very useful in delicate maneuvers; therefore, it can present several advantages. In implant dentistry, piezosurgery was first used to lift the maxillary sinus, changing the way of accessing the lateral wall of the maxillary sinus. The article aims to perform a literature review, involving current data, on piezoelectric surgery in maxillary sinus lift. It appears that piezosurgery is a positive alternative, even with negative points; but it can be used in maneuvers in the maxillary sinus. However, more analysis needs to be done, to further understand this system and address its disadvantages.